Increasing the efficiency of well killing in depleted gas condensate fields with extremely low reservoir pressures - R. A. Gasumov; E. R. Gasumov (Наука. Инновации. Технологии)
The problem is studied by the example of gas condensate fields at the final stage of development, where production wells have abnormally low reservoir pressures and their killing for repair work is a serious challenge requiring a search for new solutions. The work is motivated by the need to create a method for controlling hydrodynamic processes in a pre-blocked bottom-hole zone of the formation, for carrying out repair work in wells, preventing destruction of the reservoir formation and ensuring the preservation of its fluid-capacitance properties. The possibilities of an integrated approach to killing wells under conditions of extremely low formation pressures are considered, which includes controlling hydrodynamic processes in the “well-reservoir” system, previously blocked in the near-wellbore zone by special process fluids. It has been specified that the use of blocking fluids (with filler) helps to level the injectivity profile and form an insulating screen in the bottomhole zone of the formation, creating the necessary conditions for killing wells in order to carry out repair work in them. To control hydrodynamic processes, a mathematical model of the blocking process in the near-wellbore formation zone is proposed. It has a three-stage scheme that ensures equalization of the injectivity profile under conditions of extremely low formation pressures. The possibilities of using gel-forming blocking fluids with filler to create a temporary screen that prevents the penetration of killing fluid into highly permeable formations from abnormally low formation pressures have been explored. Based on the results of the study, we can conclude that the control of hydrodynamic processes in the near-wellbore zone of the formation at abnormally low formation pressures creates the necessary condition for effective blocking of the productive horizon in gas and gas-condensate wells, and due to the sequential treatment of the formation with a special liquid to level the injectivity profile and gel-forming blocking composition, allows one to kill the well and prevents the working fluid from penetrating into the depths of the formation during work.